Cellular Responses of Mice to Diffusion Chambers I. Reactions to Intraperitoneal Diffusion Chambers Containing Listeria monocytogenes and to Bacteria-Free Chambers - Osebold, John W. (1970)
Diffusion chambers made with membranes having a pore size of 0.22 μm were implanted in the peritoneal cavities of mice. Chambers that contained no cells induced splenic lymphoreticular hyperplasia and a proliferation of fibroblasts around the chambers. When the chambers contained the bacterium, Listeria monocytogenes, there was strong and continuous chemotaxis of phagocytic cells to the membrane surface. The tendency to incite fibrosis around the chambers containing bacteria produced a tissue reaction resembling a chronic abscess or granuloma. The important difference from a natural lesion was the prevention of direct parasite-host cell interactions. In studies on the pathogenesis of long persisting host-parasite relationships, one might successfully use diffusion chambers to investigate the role of humoral antimicrobial substances as well as the effects of chronic inflammation, with its local concentration of metabolic products and constituents of phagocytic cells. On the other hand, the presence of diffusion chambers in the tissues is an abnormal situation and changes arising from their presence may complicate the interpretations of some experiments.